THE RELATIONSHIP BETWEEN LEUKOCYTE COUNT WITH TUBERCULOSIS (TB) LESION AREA IN CHEST X-RAY EXAMINATION - Nasywa Talitha Zahran; Yuyun Yueniwati; Alfred Julius Petrarizky (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Leukocyte count is one of the hematological parameters known to help diagnose organ damage and serve as an indicator of the body's immune system. Leukocyte counts are associated with the extent of lesions in the lung fields of tuberculosis patients on Chest X-ray (CXR) examination. This study aims to evaluate whether the leukocyte count can be used as an alternative indicator for early detection and severity assessment of tuberculosis without relying on CXR results. Therefore, this study was conducted with the aim to determine the relationship between leukocyte count and TB lesion area from Chest X-ray (CXR) examination. This study is a quantitative research type of observational analysis with a cross sectional study design conducted on 60 research subjects derived from medical record data of TB patients at Saiful Anwar Hospital, Malang, from January 2022 to December 2023. The data obtained were analyzed using the Chi-Square method, which showed that there was no significant relationship between leukocyte count and the extent of TB lesions from the CXR examination (Chi-Square, p=0.706). The conclusion of this study is that leukocyte count is not associated with the description of the lesion area of TB patients.